Organizational policies on diversity and the perception of tourism professionals on LGBTQIA+ inclusion - Pereira, Gustavo Yrihoshi; Juliano, Juliano; Yokoyama, Marcos Hideyuki (Brazilian Journal of Production Engineering, 2022)
While the first social movements in defense of rights related to sexual diversity began to gain more solid outlines in the middle of the last century, it is from the 1990s onwards that studies on the behavior of the LGBTIQIA+ consumer began to draw attention to the particularities of this public and to the economic potential of this segment. In tourism, the constant demand for diversification and innovation contributed to the consolidation of a new and promising market segment. However, the literature dedicated to the relationship between tourism and the LGBTQIA+ community has left less attention to broader social aspects, such as the inclusion of diversity in tourist organizations. This case study aimed to analyze the perception of tourism professionals about the influence of sexual diversity policies in their organizations. A bibliographic review was carried out on diversity in organizations, document analysis in the main reports of diversity in the corporate environment and application of a survey with a community of tourism students, who worked in companies in the sector. Divergent perceptions were found among tourism professionals, according to the existence or non-existence of organizational actions to promote diversity. It was concluded that the dimensions evaluated are also influenced by the recognition of professionals as LGBTQIA+.